Penghargaan Islam terhadap Kesetaraan Gender: Islamic Appreciation of Gender Equality - Al Furqon (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2012)
Recently, some parties have considered that the interpretation of scholars regarding the verses about women in the Qur'an is too textual, resulting in a narrow and non-universal understanding. Among the verses that are often cited as a form of gender bias is Surah al-Nisa verse 4, which states that men are leaders of women. Meanwhile, feminists consider this verse to be a form of